Pengaruh Abu Sekam Padi Sebagai Substitusi Abu Terbang (Fly ash) Terhadap Nilai Kuat Tekan Beton Geopolimer - Agustinus Sungsang Nana Patria; Pramesta Armanisag Pangestuti; Hafidz Fachruldyarsah Basthomi (Universitas Batanghari Jambi, 2026)
Conventional concrete uses cement as the primary binding material, which produces significant carbon dioxide (CO₂) emissions and contributes to environmental problems. One environmentally friendly alternative is geopolymer concrete that utilizes pozzolanic materials such as fly ash and rice husk ash as binding materials. This study aims to determine the effect of rice husk ash as a substitution for fly ash on the compressive strength of geopolymer concrete. The research was conducted experimentally using cylindrical specimens with a diameter of 15 cm and a height of 30 cm, with rice husk ash variations of 0%, 5%, 10%, and 15% by weight of fly ash. Compressive strength testing was carried out at the ages of 7 and 28 days using a Compression Testing Machine (CTM). The results showed that increasing the percentage of rice husk ash tended to reduce the compressive strength of geopolymer concrete under both curing methods. Under ambient curing conditions, the 28-day compressive strength decreased from 15.85 MPa for GP0 to 5.66 MPa for GP15. Under oven curing conditions, the 28-day compressive strength decreased from 37.795 MPa for GP0 to 7.925 MPa for GP15. In addition, the observed crack patterns were cone and cone and split. These findings indicate that the use of rice husk ash as a partial substitution for fly ash affects the mechanical properties of geopolymer concrete, particularly its compressive strength.